ECG and echocardiographic findings in 10–15-year-old elite athletes. (29th August 2020) - Koch, Sarah; Cassel, Michael; Linné, Karsten; Mayer, Frank; Scharhag, Jürgen
Abstract: Background: Data on electrocardiographic and echocardiographic pre-participation screening findings in paediatric athletes are limited. Methods and results: 10--15 year-old athletes ( n  = 343) were screened using electro- and echocardiography. The electrocardiogram (ECG) was normal in 220 (64%), mildly abnormal in 108 (31%), and distinctly abnormal in 15 (4%) athletes. Echocardiographic upper reference limits (URL, 97.5 percentile) for the left ventricular (LV) wall thickness in 10–11-year-old boys and girls were 9–10 mm and 8–9 mm, respectively; in 12–13-year-old boys and girls 9–10 mm; and in 14–15-year-old boys and girls 10–11 mm and 9–10 mm, respectively. Three athletes were excluded from competitive sports: one for symptomatic Wolff-Parkinson-White syndrome with a normal echocardiogram; one for negative T-waves in V1 –V4 and a dilated right ventricle by echocardiography suggestive of (arrhythmogenic) right ventricular disease; and one for normal ECG and biscupid aortic valve including an aneurysm of the ascending aorta detected by echocardiography. Related to echocardiographic findings, the sensitivity and specificity of the ECG to identify cardiovascular abnormalities was 38% and 64%, respectively. The ECG's positive-predictive and negative-predictive values were 13% and 88%, respectively. The numbers needed to screen and calculated costs were 172 for ECG (€7049), 172 for echocardiography (€11, 530), and 114 combining ECG and echocardiography (€9323). Conclusions: Compared to adults, paediatric athletes presented with fewer distinctly abnormal ECGs, and there was no gender difference in paediatric athletes' ECG-pattern distribution. A combination of ECG and echocardiography for pre-participation screening of paediatric athletes is superior to ECG alone but 30% more costly.